2015
DOI: 10.1097/meg.0000000000000402
|View full text |Cite
|
Sign up to set email alerts
|

Prospective multicenter validation of the Glasgow Blatchford bleeding score in the management of patients with upper gastrointestinal hemorrhage presenting at an emergency department

Abstract: The GBS is superior compared with both Rockall scores in predicting the need for treatment in patients with suspected acute UGIH presenting at EDs in the Netherlands. Patients with a GBS of 2 or less form a subgroup of low-risk patients. These low-risk patients are eligible for outpatient management, which might reduce hospital admissions and healthcare costs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 23 publications
2
15
0
Order By: Relevance
“…In terms of predicting rebleeding, the full RS system was superior to the GBS system, which is not the same as our study. As shown by Aquarius et al, the GBS system had the optimal combination of sensitivity (99.4%) and specificity (42.4%) at a cutoff value of up to 2 as the best determinative point for mortality prediction 15. Lee et al found that the full RS system was more accurate than the GBS system for predicting mortality, same as our study.…”
Section: Discussionsupporting
confidence: 85%
“…In terms of predicting rebleeding, the full RS system was superior to the GBS system, which is not the same as our study. As shown by Aquarius et al, the GBS system had the optimal combination of sensitivity (99.4%) and specificity (42.4%) at a cutoff value of up to 2 as the best determinative point for mortality prediction 15. Lee et al found that the full RS system was more accurate than the GBS system for predicting mortality, same as our study.…”
Section: Discussionsupporting
confidence: 85%
“…The authors concluded this low-risk subgroup were eligible for outpatient management, which might reduce hospital admissions and healthcare costs. 20 Further to this, one study indicated that patients with a GBS of 2 or less could be suitable for outpatient management doubling the number of eligible patients for early discharge. 16 From our results, two patients with a GBS of 3 died within 30 days of presentation.…”
Section: Discussionmentioning
confidence: 96%
“…6 Patients with a GBS of 2 or less are considered to have a low risk and are eligible for outpatient management. 7 Although the GBS cut-off value for high-risk patients still is ambiguous, patients with a GBS greater than 7 were shown to have increased risks of significant bleeding and mortality. 8 In many studies, high-risk patients showed an extremely high mortality rate of up to 25%.…”
mentioning
confidence: 99%